How do strategic narratives shape policy adoption? Responses to China's Belt and Road Initiative. Issue 1 (10th January 2021) - van Noort, Carolijn; Colley, Thomas
Abstract: Strategic narratives are increasingly considered important for domestic and international support for foreign policy. However, debate continues about why some strategic narratives successfully shape policy outcomes, while others are rejected. How states construct strategic narratives is well established. We know less about how states appropriate the strategic narratives of others, and the role this plays in policy adoption. Addressing this, we introduce a theoretical framework to trace the relationship between strategic narratives and policy adoption. Its central premise is that a state is more likely to adopt a new policy if it can strategically narrate about it in a way that promises material gain but without undermining its ontological security. We test our framework using states' responses to China's Belt and Road Initiative (BRI). Examining the Second Belt and Road Forum in 2019, we trace how far China's strategic narratives are appropriated by multiple states – Kazakhstan, Italy, United Kingdom, Netherlands, United States, India, and Mexico. Countries appropriate China's narrative emphasis on connectivity, trade, and prosperity. However, they contest that China's intentions are benign, based on its human rights record, assertive foreign policy, and fears of indebtedness. Finally, we discuss our framework's utility in explaining what makes strategic narratives persuasive in International Relations.